Pengaruh Corporate Gorvenance Islam terhadap Tax Avoidance - Arinta, Yusvita Nena (BISNIS, 2018)
The purpose of the study was to investigate the effect of  Islamic corporate governance on tax avoidance of sharia banking in Indonesia. The data that used in this study is scendary data derived from annual financial statements and good corporate governance report of sharia banking in Indonesia during 2013-2017 period. The number of sharia banking that became sample in this study were 8 banks so there 55 research samples. The metohod of analysis that use is multiple regression analysis. The results of this study show that the elements of corporate governance that consist of  the board of commissioners, the board of commissioner meeting, the board of sharia, the board of sharia meeting, audit committee, meeting of audit comitte significantly influence the activity of tax avoidance as measured using proxy book tax gap. Other results show that the tax avoidance activity as measured with proxy book tax gap are not affected significantly by the board of commissioner meeting. Limitation of this study is use corporate governance’s proxy separately, so it can’t capture the full effect of corporate governane.